Penerapan PP 46 Tahun 2013: Adilkah Peraturan ini bagi Pelaku Usaha Mikro Kecil dan Menengah (UMKM)? - dianila oktyawati (Jurnal Gama Societa, 2018)
Taxes are the largest source of state revenues. This is indicated in the State Budget of Revenue and Expenditure (APBN) in 2017 that the target of state revenue from the tax sector is 85.6%. In Indonesia, UMKM is the most developed business in terms of its number. The existence of UMKM plays an important role in people's economic development in a country and has the potential to improve people's welfare. One of the government's efforts to increase tax revenues from the MSME sector is the enforcement of Government Regulation No. 46 of 2013. PP 46/2013 on income tax on income from businesses received or obtained by taxpayers who have certain gross revenue. Gross revenue is less than Rp 4,8 billions, - in one year. This study aims to test the fairness of the application of PP 46 on MSMEs. The analysis used is descriptive qualitative analysis. The results of this study indicate that the application of PP No. 46 is simple, easy to apply for MSMEs. But this PP is not fair. It only benefits the MSME group which has a profit margin of above 8% of the gross revenue, otherwise if the profit margin is below 8% it will be detrimental to the MSMEs. This caused in the calculation of PP 46 calculated from gross revenue, not profit, meaning if the company gets a little profit or even suffered losses will be taxed not from gross circulation. In addition, this PP also does not pay attention to the number of dependents (PTKP) in counting taxes for individual MSMEs perpetrators.